Utilization of tetanus and diphtheria serology tests in Alberta, Canada: Patterns and implications - Jamil N. Kanji; Behzad Heibati; Nathan Zelyas; Hong Yuan Zhou; Gregory J. Tyrrell; Adil Adatia (PLoS ONE, 2025)
Background Tetanus and diphtheria (Td) antibody titers can be measured to assess for seroprotection from immunization, though this is not routinely indicated. There are limited population level data on the utilization of these tests and their results. Methods This is a population level retrospective study based on laboratory data collected from patients who underwent Td antibody testing. Td IgG titer requests from May 1, 2023, to December 31, 2024, were extracted from the provincial health information system of Alberta, Canada. Td anti-toxin test requests, geometric mean titers, and vaccination status of patients who underwent testing were analyzed. Individuals with multiple tests were assessed for changes in antibody levels, and the proportion of tested individuals who were vaccinated within the past 10 years was calculated. Geometric mean titers were interpreted in relation to established thresholds for long-term protective immunity. Results A total of 2,550 patients underwent testing for tetanus (n = 2,349) and diphtheria (n = 2,093) anti-toxin antibody levels. Geometric mean titers varied widely across physician specialties, with pediatrics and Immunology showing higher proportions of recent vaccinations and higher geometric mean titers, while general practice and nephrology had lower values. Nearly 40% of diphtheria test orders in patients immunized within the past 10 years were requested by general practice (n = 336). In contrast, less than 20% of tests were ordered by nephrology (n = 153), pediatrics (n = 95), and pharmacy (n = 12). Conclusion Over half the tests were requested by general practice. Our study highlighted variability in vaccination patterns and immune responses across specialties. While antibody testing is useful for assessing protection, a considerable number of tests were performed in individuals likely to be protected by recent vaccination, pointing to inefficiencies and unnecessary healthcare spending. These findings underscore the importance of aligning test ordering practices with immunization history to optimize resource use, avoid redundant testing, support diagnostic stewardship, and inform more cost-effective public health strategies.